2019
DOI: 10.1038/s41598-019-42859-7
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast is associated with adiposity markers especially when sleep time is adequate in adolescents

Abstract: Adolescence is a critical stage of development and has an important influence on energy balance-related behaviours (EBRBs). When adolescents are associated with obesity it can lead to increased cardiometabolic risk. Here we assess if EBRBs adopted by adolescents included in a subsample are associated with markers of total and abdominal adiposity in a multicentre European study, Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA-CSS) and a Brazilian study, Brazili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
2
30
0
2
Order By: Relevance
“…Short sleep duration might be another possible reason for no significant impact of skipping breakfast on weight gain and overweight/obesity. European and Brazilian cross-sectional studies suggested that skipping breakfast was associated with BMI in adolescents with sleep duration ≥8 h/day, whereas their association was blunted in those with sleep duration <8 h [40]. Because the present study included 2.4% male and 1.3% female students who had sleep duration ≥ 8 h, skipping breakfast might not be associated with weight gain and overweight/obesity.…”
Section: Discussionmentioning
confidence: 57%
“…Short sleep duration might be another possible reason for no significant impact of skipping breakfast on weight gain and overweight/obesity. European and Brazilian cross-sectional studies suggested that skipping breakfast was associated with BMI in adolescents with sleep duration ≥8 h/day, whereas their association was blunted in those with sleep duration <8 h [40]. Because the present study included 2.4% male and 1.3% female students who had sleep duration ≥ 8 h, skipping breakfast might not be associated with weight gain and overweight/obesity.…”
Section: Discussionmentioning
confidence: 57%
“…Some studies have reported associations between skipping breakfast and adiposity in children [14][15][16][17]. For instance, in European adolescents, those who are used to regularly consuming breakfast had a low body fat percentage and healthy cardiovascular profile as compared with those who skipped breakfast, especially in males [18].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that skipping breakfast were significantly higher in children who reported poor sleep 52 . Skipping breakfast was associated with total and abdominal obesity in adolescents independent of sleep duration 54 . Prevalence of obesity has reached epidemic proportions across all gender, age and ethnic groups 55 .…”
Section: <001 [A-bc][b-c]mentioning
confidence: 89%